Determination of the lifetime of ropes used in mining industry by statistical methods - Costandoiu, R.; Adam, C. D. (NTU "KhPI", 2009)
Statistics made on the basis of the operation of a cable mining extraction.
Определение срока службы строп, используемых в горнодобывающей промышленности, статистическими методами